The Boxty Paradox: Everything, Everywhere, All At Once - Boermans, Mary-Anne (Petits Propos Culinaires, 2023)
This paper takes as its subject the Irish potato dish of Boxty and draws upon the thousands of transcripts available in the Irish National Folklore Collection (Schools) as its primary sources. Investigations reveal that, far from being a simple dish, the transcripts unveil dozens of different types of Boxty from all over the country, as well as the geographic spread of the many names by which a single style of Boxty is known. In addition, this unique collection of personal testimonies reveals just how inextricably intertwined Boxty is with the history, life, culture and traditions of the people of Ireland. From music and poetry, to food preparation and cooking utensils, the privations of The Famine, high days and holidays, the turning of the seasons, celebrations and social events. This paper demonstrates the impossibility of studying Boxty in isolation, and that in fact, the dish of Boxty is symbolic of both Ireland’s history and of the Irish people themselves. Richly illustrated with quotations from the transcripts, this paper is also supported by further extracts in the Appendices which, due to their length, are available at <https://dejafood.uk/books/>.